2013
DOI: 10.4103/0973-1296.111265
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Ficus racemosa stem bark against doxorubucin-induced renal and testicular toxicity

Abstract: Background:Ficus racemosa Linn. (Moraceae) bark is a rich source of phenolic compounds known to possess potential antioxidant activity offering numerous health benefits.Materials and Methods:The present study evaluated the protective effects of sequential acetone extract of Ficus racemosa bark at two doses (FR250; 250 mg kg-1 and FR500; 500 mg kg-1 p.o.) against doxorubicin-induced renal and testicular toxicity in rats.Results:Doxorubicin administration resulted in significant decrease (P ≤ 0.05) in total prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…These findings are in accordance with the earlier scientists (kato et al, (2001), Patil et al, (2009), Bashandy and Amin (2012, and Ahmed et al, (2013). The interstitial tissue was widened due to severe edema and vacuoles were noticed, this could be attributed to endothelial dysfunction and oxidative stress in the vascular wall as reported by Venderamani et al, (2010) and Brilhantae et al, (2011).…”
Section: Ultra Structuresupporting
confidence: 82%
“…These findings are in accordance with the earlier scientists (kato et al, (2001), Patil et al, (2009), Bashandy and Amin (2012, and Ahmed et al, (2013). The interstitial tissue was widened due to severe edema and vacuoles were noticed, this could be attributed to endothelial dysfunction and oxidative stress in the vascular wall as reported by Venderamani et al, (2010) and Brilhantae et al, (2011).…”
Section: Ultra Structuresupporting
confidence: 82%
“…The results of Ezzat et al, (2005) showed that serum ALP activity is significantly increased upon treatment of mice with DOXO versus the controls. DOXO is also known as nephrotoxic candidate that produces chronic progressive glomerular disease manifested by increased plasma creatinine and urea levels in association with extensive glomerular lesions, tubular dilatation, vacuolization of renal glomeruli, protein deposits in tubular lumen and stromal fibrosis (Injac et al, 2008;Ahmed et al, 2013). These findings explained the present results of the insignificant change in serum urea and creatinine levels in HCC group treated with DOXO (1).…”
Section: Biological Assay Biochemistrysupporting
confidence: 64%
“…Because of its known antioxidant properties, the effects of Ficus racemosa on the kidneys and testes have been assessed, and this plant was shown to reduce DXR-induced damage in both these organs. However, it is not always possible to identify the active ingredient in plant extracts, and the authors of this previous study stressed that further studies were required to identify the active ingredient(s) [20]. In our study, we chose to use isolated RA to evaluate the effectiveness of specific molecules.…”
Section: Discussionmentioning
confidence: 99%